The Foraminifera Fossil Record of the Sedimentary Rock at Kotadjawa, Lampung, Indonesia: The Significance of Marine Paleontological Insight - Harbowo, Danni Gathot; Sitinjak, Eri Sarmantua (Jurnal Riset Biologi dan Aplikasinya, 2024)
Kotadjawa, located on the west coast of Lampung, directly faces the Indian Ocean. Lithified calcareous sedimentary beds are prevalently outcropped along this coastline. These beds likely belong to the Simpangaur Formation, which may be associated with the paleocoastal depositional environment and tectonic uplift of the Indian Ocean. Therefore, we investigated the paleontological record, focusing on foraminifera as potential indicators of the paleoenvironment. This study aimed to identify, record, and calculate the relative abundance of benthic foraminifera in the sedimentary beds of Kotadjawa, Lampung. The samples were prepared via chemical treatment of 10% H2O2 for 48 hours. Our results revealed a diversity of benthic foraminiferal fossils within the sedimentary rock. Notably, 11 benthic foraminifera genera were fossilized in the observed outcrop: Textularia (18.4%), Sigmoilopsis (16.5%), Rectobolivina (15.4%), Uvigerina (15.5%), Nodosaria (14.5%), Elphidium (11.5%), Lenticulina (7.7%), Hormosina (6.8%), Bolivina (6.8%), and Globobulimina (5.8%). These results suggested that the sedimentary beds exposed in our study area ranging from the foreshore to the deep ocean floor ecosystem. This suggests that a sediment mixing event, possibly triggered by a paleocatastrophic event, influenced the deposition of these beds. This study provides new insights into marine paleoenvironmental conditions and paleocatastrophic events along the west coast of Lampung, Sumatra.